STRATEGI PEMASARAN LEMBAGA PENDIDIKAN TINGGI SWASTA - Ariwibowo, Muhamad Eko (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
In fact, many scholars are unemployed, bankrupt colleges, and fierce competition. Therefore, higher education institutions should use marketing strategies. This study aims to analyze the marketing strategies of Pamulang University. The research method uses qualitative, students are samples, simple random sampling techniques are used, instruments used are questionnaires and descriptive analysis methods. The results of the study suggest that the respondents' demographics influence the accuracy of the marketing strategies used, low cost is the main marketing strategy, costs and education systems are word of mouth proxies, and technology systems are supporting marketing strategies. This research proves that low cost marketing strategies are very effective in gaining market share. But it needs to be supported by other marketing strategies, such as word of mouth and technology systems